Druckprojekte indigener Sprachen im Vizekönigreich Peru: Publizierbarkeit und unveröffentlichte Manuskripte - Gehbald, Agnes (Anuario de Historia de América Latina, 2023)
This article examines unpublished manuscripts and failed printing projects in the languages of the former Inca empire up to the beginning of the 19th century. Although the original reason for establishing a printing press in Lima in 1584 was to publish texts in indigenous languages, the colonial context would restrict such printing in various ways. After an initial period which saw numerous pastoral and linguistic publications, a bibliographical analysis reveals that printing in indigenous languages declined considerably from the mid-17th century onwards. Besides publications in Quechua and Aymara, we know of only few printed texts in Mochica (Yunga) and Puquina from the colonial era, whereas further linguistic material dedicated to these languages circulated in manuscript form. Only between 1810 and 1822 would bilingual publications increase again, in the form of political proclamations written in the context of the independence movements. In contrast, the spread of Spanish contributed to the linguistic cohesion of the various viceroyalties and formed a key part of the geopolitics of colonisation and evangelisation. After the shift towards a more monolingual language policy – which intensified after rebellions in the Andes in the late 18th century – there were almost no more new publications in indigenous languages in Lima. As a case study, the failed publication project of a Quechua grammar by José Manuel Bermúdez in Lima in 1793 demonstrates how the attempt to renew the publication of indigenous-language texts, and thus to diversify the range of works available, ultimately proved unfeasible. By examining unpublished manuscripts and focusing on such failed printing projects like that of Bermúdez, this article enhances our knowledge of the printing culture in the past.